MODIFIKASI TEKNOLOGI UMPAN BUATAN UNTUK PENANGKAPAN IKAN PELAGIS PADA PERIKANAN PANCING TONDA DI PERAIRAN MAMUJU - Kantun, Wayan (LPPM Institut Pendidikan Nusantara Global, 2023)
Fishing technology consists of fishing gear and auxiliary fishing gear which are implemented using various methods according to the objectives to be achieved. The application of fishing technology aims to increase the effectiveness, efficiency and productivity of fishing. One fishing technology is the use of artificial bait as an attractant to attract the attention of fish so that they can easily be caught and preyed on by pelagic fish. This service is carried out in Mamuju waters for the purpose of catching pelagic fish. The service was carried out using trolling fishing gear. The results of the service showed that the results obtained were skipjack tuna (Katsuwonus pelamis), krai tuna (Auxis thazard) and yellowfin tuna (Thunnus albacares). The largest catches were obtained from fishing ground in oceanic waters with water depths above 200 m.